Factors Affecting the Combined Spinal Epidural Block Spreading Level - Önal, Selami Ateş; Yaşar, Mehmet Akif; Akin, Mustafa; Bayar, Mustafa Kemal; Erhan, Ömer Lütfi; Özmiş, Metin (My University, 2003)
Combined spinal epidural block (CSEB) can enhance the spreading level of local anaesthetic (LA). Eighty patients (21-78 yr, ASA physical status I and II) were randomly allocated to four groups of 20 patients each. CSEB was achieved at the L3-L4 interspace with the patient in the sitting position. Study 1: to assess the compressive effect of the epidural LA on the dural bag: Group I/Study (1-S): CSEB with 0.5% plain bupivacaine 4 mL in the subarachnoid space, 0.9% saline 20 mL in the epidural space; Group II/Control (1-C): Spinal block with 0.5% plain bupivacaine 4 mL in the subarachnoid space; Study 2: to assess the passage of the LA through the dural hole: Group III/ Study (2-S): CSEB with 0.9% saline 4 mL in the subarachnoid space, 0.5% bupivacaine 20 mL in the epidural space; Group IV/Control (2-C): Epidural block with 0.5% bupivacaine 20 mL in the epidural space. Assessment of the spreading levels of block was performed at 5 min intervals during 20 minutes. Comparisons of the spreading levels were significantly differents between the Groups 1-S and 1-C at 5 min and 10 min; significantly differents between the Groups 2-S and 2-C at 15 min and 20 min (p<0.05). Linear regression analysis revealed significant correlation between body mass index and the cephalic spreading level of CSEB. We confirmed that increasing the spinal sensitive block level with CSEB may be done by the compression of the volume given to epidural space which causes enhanced total spreading and also by the entrance of the bupivacaine from dural hole which was given to epidural space.
Kombine Spinal Epidural Anestezide Yayilim Seviyesini Etkileyen Faktörler
Keywords: Bupivacaine; Combined spinal epidural block; Spreading level